2019
DOI: 10.1111/bcpt.13322
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of registered drug packs with Maastricht V/Florence Consensus Report and national treatment guidelines for management of Helicobacter pylori infection

Abstract: High prevalence of Helicobacter pylori infection, the complexity for its treatment, poor correlation of registered drug packs or poor patient adherence to the treatment may contribute to antibiotic resistance and healthcare costs. The aim of the present study was to investigate whether registered drug packs are in accordance with European and national guidelines for H pylori eradication with reference to the number of drug units. In this study, we considered treatment options for the management of H pylori inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
3

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 38 publications
1
8
0
3
Order By: Relevance
“…6 Recent studies have raised question about the ability of physicians to follow guidelines due to the limited availability of appropriate drug packs. 7,8 This stresses the importance of different skills needed among physicians and an ever-growing need for new and up-to-date information and education. Furthermore, with most of the antibiotic consumption being in primary care, 9 pharmacists have a unique opportunity to contribute to the management of AMR as well to affect patients' adherence to treatment and management of leftover antimicrobials.…”
Section: Introductionmentioning
confidence: 99%
“…6 Recent studies have raised question about the ability of physicians to follow guidelines due to the limited availability of appropriate drug packs. 7,8 This stresses the importance of different skills needed among physicians and an ever-growing need for new and up-to-date information and education. Furthermore, with most of the antibiotic consumption being in primary care, 9 pharmacists have a unique opportunity to contribute to the management of AMR as well to affect patients' adherence to treatment and management of leftover antimicrobials.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous research showed poor adherence of drug packaging with European and national guidelines for management of H pylori infection for a portion of EU countries. Unavailability of drugs that are an integral part of the first treatment line is also important problem for implementation of Maastricht V/Florence consensus report in clinical practice 30,31 . Furthermore, most recent data on H. pylori resistance rate in Croatia were published in 2012 13 …”
Section: Discussionmentioning
confidence: 99%
“…Пациентам с высоким риском геморрагических осложнений необходима коррекция модифицируемых ФР ЖКК: эрадикация H. pylori при наличии хронического хеликобактерного гастрита (показана всем пациентам согласно Маастрихтскому консенсусу V); отказ или минимизация приема НПВП и глюкокортикостероидов; переход на более безопасные для ЖКТ НПВП и антиагреганты (высокоселективные ингибиторы циклооксигеназы-2, блокаторы рецепторов к аденозиндифосфату), использование гастропротективной и кислотосупрессивной терапии [15,29,30,32]. Общераспространенной клинической практикой является назначение ингибиторов протонной помпы (ИПП) для профилактики и лечения эрозивно-язвенных поражений пищевода, желудка и двенадцатиперстной кишки.…”
Section: управление рисками жкк у кардиологических пациентовunclassified
“…ИПП должны назначаться всем пациентам, набравшим ≥3 баллов по шкале HAS-BLED. Данные препараты существенно не отличаются по эффективности, однако при лечении полиморбидных пациентов с полипрагмазией целесообразно выбирать ИПП, имеющие минимальные риски неблагоприятных лекарственных взаимодействий -рабепразол и пантопразол [15,29,30,[32][33][34].…”
Section: управление рисками жкк у кардиологических пациентовunclassified